Two siblings with familial neuroblastoma with distinct clinical phenotypes harboring an ALK germline mutation. Issue 12 (22nd October 2018) - Kudo, Ko; Ueno, Hiroo; Sato, Tomohiko; Kubo, Kaori; Kanezaki, Rika; Kobayashi, Akie; Kamio, Takuya; Sasaki, Shinya; Terui, Kiminori; Kurose, Akira; Yoshida, Kenichi; Shiozawa, Yusuke; et al.
Abstract : The authors report two siblings with familial neuroblastoma with a germline R1275Q mutation of the tyrosine kinase domain of ALK . Whole exome sequencing and copy number variation assay were performed to investigate genetic alterations in the two cases. No common somatic mutations or gene polymorphisms related to the tumorigenesis of neuroblastoma were detected. A distinct pattern involving both segmental chromosomal alteration and MYCN amplification was detected. The diversity of biological behavior of familial neuroblastoma harboring a germline ALK mutation may depend on conventional prognostic factors, such as segmental chromosomal alterations and MYCN amplification, rather than additional acquired mutations.